Intervention in a psychological support group with harassed workers - Albanaes, Patricia (2017)
Bullying at work is a form of violence which consists in prolonged and repeated exposure of workers to offensive and humiliating situations and may be a trigger of psychological distress in many individuals and groups. Literature in the field identifies support groups as an emergent treatment alternative with positive results. This study aimed to qualitatively describe the development of a support group for people who suffered bullying at work in a public university in the South of Brazil. The group was composed of 5 women who took part in 8 meetings during 2014 and 2015. The main results of this intervention provide information about bullying at work, developing new coping strategies and the development of a framework of mutual support among the participants.